Beneficial Rhizobacterium Triggers Induced Systemic Resistance of Maize to Gibberella Stalk Rot via Calcium Signaling - Yu Cao; Yinying Wang; Cuilin Gui; Kilemi Jessee Nguvo; Liang Ma; Qing Wang; Qirong Shen; Ruifu Zhang; Xiquan Gao (Molecular Plant-Microbe Interactions, 2023)
Gibberella stalk rot (GSR) caused by the fungus Fusarium graminearum is a devastating disease of maize (Zea mays L.), but we lack efficient methods to control this disease. Biological control agents, including beneficial microorganisms, can be used as an effective and eco-friendly approach to manage crop diseases. For example, Bacillus velezensis SQR9, a bacterial strain isolated from the rhizosphere of cucumber plants, promotes growth and suppresses diseases in several plant species. However, it is not known whether and how SQR9 affects maize resistance to GSR. In this study, we found that treatment with SQR9 increased maize resistance to GSR by activating maize induced systemic resistance (ISR). RNA-seq and quantitative reverse transcription-PCR analysis showed that phenylpropanoid biosynthesis, amino acid metabolism, and plant-pathogen interaction pathways were enriched in the root upon colonization by SQR9. Also, several genes associated with calcium signaling pathways were up-regulated by SQR9 treatment. However, the calcium signaling inhibitor LaCl3 weakened the SQR9-activated ISR. Our data suggest that the calcium signaling pathway contributes to maize GSR resistance via the activation of ISR induced by SQR9. [Graphic: see text] Copyright © 2023 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.